ANTRODIA CINNAMOMEA EXTRACT ATTENUATES CARBON TETRACHLORIDE-INDUCED CHRONIC LIVER FIBROSIS IN SPRAGUE-DAWLEY RATS - Lan, Chuan-Ching; Tsai, Yueh-Ting; Huang, Chun-Chih (African Journal of Traditional, Complementary and Alternative Medicines, 2015)
Background: Antrodia cinnamomea (AC) mycelia have been traditionally used by majority of the indigenous populace in Taiwan for symptoms including treating alcohol intoxication. Other beneficial effects have been studied at some point. The present study evaluated the hepato-protection effects in Sprague-Dawley rats.Methods: The model used carbon tetrachloride (CCl4) to induce a chronic liver injury in male rats. Animals were treated with silymarin 200 mg/kg and AC mycelia at doses of 206, 619 and 1,032 mg/kg. The effects of AC on hepatic enzyme markers alanine and aspartate aminotransferase (ALT and AST) and other biochemical parameters were measured in the CCl4 -induced rats. Results: AC demonstrated a hepato-protective effect by decreasing ALT and AST levels and increasing albumin levels in CCl4 treated rats. The effects of AC on the activity of antioxidant enzymes were evaluated. AC administration restored the activities of catalase (CAT), glutathione peroxidase (GPx) and glutathione reductase (GrD). The degree of liver fibrosis was significantly reduced by AC administration in CCl4 -treated rats. Conclusion: These results suggest that AC could protect the hepatocytes from CCl4 -induced liver injury likely via an antioxidant mechanism.